Insights into improving photoelectrochemical water-splitting performance using hematite anode - Devi, Hemam Rachna (2022)
Designing an efficient photoanode is of great importance for photoassisted solar water splitting. Herein, a series of modifications to a nanorod structure hematite, to be used as anode for photoelectrochemical (PEC) water-splitting reactions is designed. Ti doping, oxygen vacancy formation by N2 treatment, TiO2 passivation, and FeOOH cocatalyst decoration are explored for their roles and contributions to the improvement of the PEC water oxidation performance. It is found that Ti doping and N2 treatment can greatly increase the charge carrier density, which has boosted the photocurrent. TiO2 passivation enhances the photovoltage, resulting in a cathodic shift in the onset potential (≈170 mV with respect to prepassivation). Further, the FeOOH cocatalyst decoration improves the reaction kinetics, thereby improving the overall photoassisted water oxidation performance.